Identifying collocation issues in English L2 research article writing - Pinto, Paula Tavares [UNESP]; Rees, Geraint Paul; Frankenberg-Garcia, Ana; Charles, M.; Frankenberg-Garcia, A. (Routledge, 2021)
Although there are numerous collocation studies that examine texts by L2 students, little is known about how mature researchers writing authentic L2 English texts in their fields use collocations. This chapter investigates collocation issues in L2 English research papers in Brazil. Its starting point was the compilation of the Brazilian Academic Corpus of English (BrACE), a 906,035-word multidisciplinary corpus of journal articles written in English that have been published in Brazilian journals. The most frequent noun collocations in this corpus were contrasted with those used in international academic publications. No evidence of systematic miscollocation was found in the published papers represented in BrACE. However, many general academic English collocations were conspicuous by their absence from BrACE, including collocations with L1 Portuguese cognates. We also observed that the collocations in BrACE were less diverse and tended to score higher in terms of strength of association than their equivalents in the reference data. Our findings indicate that although feedback on miscollocations can be relevant to unedited drafts, L2 English research writers would also benefit from suggestions to expand their collocation repertoire, enhance their perceptions of collocation strength, and offset collocation avoidance.